SEISMIC PERFORMANCE OF MAJOR COMPONENTS IN CRITICAL SYSTEM OF SINAGAMA IRRADIATION PLANT, PENINSULAR MALAYSIA - MALACHI, TING JIA JING (Universiti Malaysia Sarawak (UNIMAS), 2020)
Earthquake has been known to cause much damage to industrial facilities. This research aims to assess the seismic response for the source storage pool cooling system of the Cobalt-60 Irradiator in the Sinagama industrial building, Peninsular Malaysia. Said industrial facility houses radioactive materials, and its operation is crucial to various sectors, such as the medical sector, where it is used to sterilize medical equipment. All the parts in the source storage pool cooling system are modelled and analysed by means of finite element analysis. The parts include the concrete storage pool, heat exchanger, pool water tank, steel piping system, water chiller compressor, and water pump. All the parts and the system is subjected to seismic loading, where the earthquake time history is taken from the Eregli station for the Kocaeli earthquake in Turkey. Ground motion with peak ground acceleration of 0.10g, 0.20g, 0.50g, and 1.00g is used, and the finite element analysis is conducted using Abaqus/CAE 6.14 software. The parameters that are obtained are maximum principal stress, acceleration, and displacement. The results obtained indicate that the materials that make up the parts in the system will not fail, even when subjected to ground motion with peak ground acceleration of 1.00g. Nonetheless, attention needs to be given to the connections of the parts and components in the source storage pool cooling system, as it is found that the area that joins the steel pipes and the pool water tank is subjected to high levels of stress. This indicates that the steel piping system is the critical part in the source storage pool cooling system.